Size‐Dependent Cobalt Catalyst for Lithium Sulfur Batteries: From Single Atoms to Nanoclusters and Nanoparticles. Issue 10 (1st September 2021) - Zhou, Xing; Meng, Ruijin; Zhong, Ning; Yin, Shuangfeng; Ma, Guoqiang; Liang, Xiao
Abstract: The sulfur redox conversion with catalytically improved kinetics is promising to mitigate the polysulfides shuttling. While the size of electrocatalyst always brings different catalytic behaviors for various heterogeneous catalytic reactions, it is yet to be explored for Li‐S batteries. Herein, a systematical study of size‐dependent catalytic activity toward polysulfides conversion and the relevance to electrochemical performance are reported, by constructing Co catalysts with different atomic scales from single atoms, atomic clusters to nanoparticles. Fundamental electrocatalytic studies are focused by probing the reduction kinetics and activation energies of sulfur chemistry. The single atomic Co shows the best charge transfer/kinetic toward sulfur redox, especially for the rate‐determining reaction (Li2 S4  ↔ Li2 S) as demonstrated by the significantly lowered energy barrier for Li2 S nucleation/dissolution. This is owing to stronger geometric deformation of the catalyst with lower aggregation extent when it interacts with sulfur species, thus leading to decreased Gibbs free energy changes as elucidated by DFT calculations. The superior catalytic activity of single atomic Co promises a high specific capacity (4.98 mAh cm −2 ) at an areal loading of 4.3 mg cm −2 over long‐term cycling. The finding emphasizes the significance of the size‐dependent catalytic activity to the reaction kinetics and the overall performance of Li‐S batteries. Abstract : The size‐dependent catalytic activities toward polysulfide conversion and their relevance to the electrochemical performance of lithium sulfur batteries are elucidated by Co catalyst with various extents of atomic aggregation. Single atom shows the highest catalytic activity toward the sulfur redox process, which is followed by nanoclusters and nanoparticles.